LIGHT-INDUCED CHANGES IN MOLECULAR ARSENIC SULFIDES: STATE OF THE ART AND NEW EVIDENCE BY SINGLE-CRYSTAL X-RAY DIFFRACTION - Bonazzi P.; Bindi L.; Pratesi G.; Menchetti S. (My University, 2006)
Light-induced structural changes in single crystals belonging to the β-As4S4-As8S9 series and in a crystal of synthetic β-AS4S3 were monitored step by step by determining the unit-cell dimensions. A marked increase of unit-cell volume as a function of exposure time was observed for all the crystals belonging to the β-AS4 S4-As8S9 series except for stoichiometric alacranite (As8S9). No significant change upon long exposures to light was observed for the synthetic β-AS4S3 crystal. Crystal structure refinements were carried out for crystals with different composition at selected steps of the light-induced process. The structural results clearly showed that the percentage of the As4S3, molecule in the structure increases when a crystal is exposed to light. Therefore, the increment of the unit-cell volume induced by light exposure appears to be related to a random replacement of As4S5 for As4S4 in the structure according to the reaction 5As4S4 + 3O2 → 4As4S5 + 2As2O3. The results obtained in the present study combined with a critical review of data previously published indicate that the As4S4 molecule is able to incorporate sulfur to convert to As4S5 upon exposure to light, whereas either As4S3 or As4 S5 molecules do not go undergo any modification. It appears that the extent of sulfur incorporation is strictly controlled by the type of molecular packing as well as by the kind of molecule. A final, complete conversion to pararealgar was observed only for pure β-As4S4, whereas non-stoichiometric As8S9-x crystals initially containing variable amounts of β-As4S4 microdomains convert only partially to pararealgar upon light exposure.
Keywords: β-AS4S4; ALACRANITE; ARSENIC SULFIDES; CRYSTAL STRUCTURE; LIGHT-INDUCED ALTERATION; XRD DATA